Autowizerunek po katastrofie. Zofia Kossak-Szczucka i Jerzy Andrzejewski: dwa polskie świadectwa Zagłady z lat 40. - Żukowski, Tomasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
As far as the question of the Holocaust is concerned, the Polish culture is characterised by some peculiar feature. On the one hand, it embraces the texts which quite uncompromisingly describe the Polish role in extermination, noticing a continuum between collective discriminating behaviours of the non-Jewish part of the society and the exterminating activities of the Nazis. Such voices deconstruct narration, in which the Polish majority remains an isolated, bystanding and passive witness of the Holocaust, and demonstrate some forms of participation. On the other hand, the message of this kind does not permeate into social consciousness, does not become known and does not improve the knowledge of the society about itself. The studies of Protest by Zofia Kossak-Szczucka and Wielki Tydzień (“Holy Week”) by Jerzy Andrzejewski are used for the description of the mechanism of this “becoming acquainted”. A key role in this mechanism is played by preoccupation with self-image of the group. The Holocaust, to a certain degree, undermined the obviousness of Polish discriminating practices towards Jews. In the awareness of elites there appeared a premonition of other criteria of evaluation of Polish behaviours, going beyond the mentioned practices (a phantasm “eyes of the world”). In the light of such criteria, the attitude towards exterminated Jews proves to be discrediting. At the same time, there appear narrations whose aim is to restore the order of discrimination and the hierarchies connected with it, which comes down to forcing the victims into inferior position—in contrast to the dominating majority—and concealing the knowledge about participation in the crime. Consequently, culture remains in the state of unrest. Unwanted knowledge (and the feeling of guilt) returns and the attempts to become purified by the renewed concealment and repudiation of the awareness of evil always prove unsuccessful. The signs of repudiation are the recurring symptoms and repetitions of the same scenario of denial of never clearly stated accusations.